Natural products R&D at UMP - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Mohamad Najib, Mohammad Nor (Penerbit UMP, 2008)
Returning to Malaysia from a lengthy stint of study and work in United States, Mashitah Mohd. Yusoff would never have imagined stepping into burgeoning naturall product of R&D world.